Role of hypoxia-related genes and immune infiltration in intervertebral disc degeneration: molecular mechanisms and diagnostic potential - Kai Zhou; Jiaxiang Zhou; XianJin Luo; Yan Chen; Jian Ao; Wei Wu; Bo Yang; Zhongyuan He (Frontiers in Immunology)
ObjectiveTo investigate the role of hypoxia-related genes and immune infiltration in intervertebral disc degeneration (IDD) to identify molecular mechanisms and potential therapeutic targets.MethodsUsing GEO data, IDD-related gene expression datasets were analyzed for hypoxia-related differentially expressed genes (HRDEGs). Logistic regression and receiver operating characteristic (ROC) analyses were employed to evaluate the diagnostic potential of HRDEGs. Consensus clustering further delineated molecular subtypes of IDD. Functional enrichment analyses (GO, KEGG, GSEA) highlighted key pathways. Protein-protein interaction (PPI) networks were built in STRING and visualized with Cytoscape, identifying core genes with MCODE and CytoHubba. Immune cell infiltration was analyzed with CIBERSORT and ssGSEA to correlate immune cells with hypoxia-related genes. To validate the expression of potential biomarkers, qPCR and immunohistochemistry were conducted on human intervertebral disc tissue samples.ResultsThe integration of GSE150408 and GSE124272 datasets with batch effect removal enabled differential gene analysis, identifying nine HRDEGs, including RCOR2, STAT3, and NOTCH1. Logistic regression analysis demonstrated that these genes have high diagnostic efficacy for IDD. Co-expression and clustering analyses revealed two distinct molecular subtypes in IDD, each characterized by unique gene expression and immune infiltration profiles. Functional and pathway enrichment analyses also showed that these DEGs are involved in pathways regulating TP53 transcription, oxidative phosphorylation, and MAPK signaling, contributing to IDD pathology.ConclusionsHypoxia-related genes, particularly RCOR2, STAT3, and NOTCH1, play a significant role in the pathology of IDD and may serve as valuable diagnostic biomarkers and therapeutic targets, with distinct immune infiltration patterns associated with different IDD subtypes.